2020
DOI: 10.1111/liv.14626
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function is associated with fibrosis severity in patients with biopsy‐proven nonalcoholic fatty liver disease

Abstract: Background & Aims The association between nonalcoholic fatty liver disease (NAFLD) and pulmonary function remains elusive because of the heterogeneous spectrum and inaccurate diagnostic methods of NAFLD, and insufficient pulmonary function data. We conducted this study to identify the association between histological severity of NAFLD and pulmonary function. Methods This study included patients ≥18 years old with baseline pulmonary function data between August 2014 and July 2019 within a biopsy‐evaluated prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
(36 reference statements)
1
8
0
Order By: Relevance
“…It is interesting that sarcopenia in patients with COPD is associated with an increased risk of NAFLD and more severe fibrosis independent of lung function and metabolic characteristics [ 228 ]. Moreover, worsening histologic severity of NAFLD, especially at the fibrosis stage, is accompanied by decreased lung function [ 229 ].…”
Section: Lipid Metabolism Disorders In the Development And Progression Of Copdmentioning
confidence: 99%
“…It is interesting that sarcopenia in patients with COPD is associated with an increased risk of NAFLD and more severe fibrosis independent of lung function and metabolic characteristics [ 228 ]. Moreover, worsening histologic severity of NAFLD, especially at the fibrosis stage, is accompanied by decreased lung function [ 229 ].…”
Section: Lipid Metabolism Disorders In the Development And Progression Of Copdmentioning
confidence: 99%
“…The positive relationship between NAFLD and pulmonary dysfunction has been well established by different types of observations, including a cross-sectional study using the data from the third National Health and Nutrition Examination Survey (NHANES III) involving 9976 participating adults [ 9 ], meta-analyzing data from five cross-sectional studies and one longitudinal study involving 133,707 individuals [ 30 ], and a prospective study using liver biopsy [ 31 ]. Likewise, the present study observed reduced pulmonary function in the NAFLD cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence indicates that lung function impairment is related to the presence of NAFLD or the histological severity of NAFLD (i.e., fibrosis severity). 10 Many cross-sectional studies have reported that NAFLD has a significant correlation with lung diseases with obstructive or restrictive physiology. 17 In a recent cohort study, the FEV 1 % of the predicted value was classified into quartiles, and the incidence of NAFLD was higher in the group with a lower quartile of FEV 1 .…”
Section: Discussionmentioning
confidence: 99%
“… 9 When analyzing histological data from NAFLD patients, the relationship between hepatic steatosis and lung function impairment might be substantially confounded by factors related to metabolic syndrome; however, fibrosis severity was independently associated with FVC impairment. 10 Therefore, the association between lung function impairment and NAFLD may be partly explained by the mechanisms underlying metabolic syndrome or hepatic fibrosis. However, since lung function is a dynamic variable that changes over time, the results of any cross-sectional analysis of the relationship between lung function and NAFLD should be interpreted with caution.…”
Section: Introductionmentioning
confidence: 99%